Same-Sex Relationships, DOMA, and the Tax Code: Rethinking the Relevance of DOMA to Straight Couples - Terry, Keeva (Columbia Journal of Gender and Law, 2011)
According to Professor Derrick Bell’s seminal article describing his Interest Convergence Theory, the interests of Blacks are only accommodated when they coincide with the interests of Whites. By analogy, the interests of same-sex couples are only accommodated when they coincide with the interests of heterosexual couples. The elimination of discriminatory provisions that cause heterosexual married couples to pay more federal income tax than their same-sex counterparts might just be the mutually beneficial interest necessary to prompt Congress to recognize same-sex legal unions. Current federal income tax laws require certain heterosexual married couples to pay more federal income tax than domestic partners3 and same-sex married couples who earn identical incomes. Most domestic partners are same-sex couples not allowed to marry one another. In an earlier article, I recommended that Congress create a new federal income tax filing category to eliminate these disparities and to equalize the tax liability between heterosexual married couples and their same-sex counterparts. If Congress finds this recommendation untenable, this Article proposes another solution to mitigate these inequalities: Repeal Section 3 of the Defense of Marriage Act (“DOMA”) which, for federal purposes, limits the definition of marriage to heterosexual marriage (“DOMA’s Marriage Definition”).